22 - Reflections on the Changing Patterns of Care for Orphans: Catrine Christiansen - Catrine Christiansen (CODESRIA Bulletin, 2003)
becoming orphans or indirectly by, for example, having to share meagre household resources with orphaned relatives In such circumstances the traditional extended family mechanisms are strained to the utmost, and it is not uncommon for adults to refuse to take care of orphaned relatives. While the extended family system seems to be disintegrating, numerous non-governmental organisations have enhanced their capacity to care for children affected by Aids, especially orphans. Susan Hunter (1990) argued that orphans could be studied as a window onto the Aids epidemic. Likewise the patterns of care for orphans can be understood as a window onto the situation of families and other social networks.Research on patterns of childcare for orphans has produced knowledge on the immediate impacts on orphans’ health (including their psycho-social situation), education, nutrition and vulnerability to HIV. However research on the long-term consequences of the care given to orphans and other vulnerable children, such as how childcare by people not belonging to the extended family influences children’s long-term well-being, competences and sociality, is comparatively absent. Besides the obvious time constraints the literature on changing patterns of childcare is often neither contextualised in the local setting nor in social science. However such in-depth knowledge is crucial. The phenomenon of a large number of children growing up as orphans poses new problems for development at local, regional and national levels. For families, communities, national authorities and aid organisations a central aspect is the network of links between childcare and sociality, particularly the long-term influence of changing patterns of childcare for the organisation of civil society. This paper addresses two central issues that have been neglected in the new field of Aids orphans: c ing concepts of care and the long-term influence of Aids orphans on emerging institutional settings for childcare.